Analysis Of The Difference In The Quality Of Beef Randang With The Use Of Local Beef And Imported Beef - Aliah, Muhafizatul; Elida, Elida (Universitas Negeri Padang, 2022)
This study aims to determine the differences in the quality of shape, color, aroma, texture and taste of randang with the use of local beef and imported beef. The method used in this study is an experimental method in the form of an organoleptic test. In this study, three repetitions were carried out which were assessed by 5 expert panelists. The results of this study on the quality of the shape of randang are in the same category, namely, quite square with a value of 3.27; and for the color quality of the inner flesh, it is in the moderately reddish-brown category with values of 3.47 and 3.33; for the color of randang bran, it is in the fairly dark brown category with a value of 3.20 and 2.93; and the aroma of randang is in the same category, namely fragrant randang with a value of 3.67 and 3.60; then the texture of the randang meat is in the fairly tender category with a value of 2.87 and 3.20; randang bran is in the fairly dry category with the same value of 3.00; and the taste of bran randang is in the savory category with a value of 3.67 and 3.73; the taste of randang meat is in the category of pervasive spices with the same value, which is 3.67. After conducting research using the two types of meat, and analyzing the T test, it can be stated that there is no significant difference in the results of randang with the use of local beef and imported beef